Body composition and inflammation variables as the potential prognostic factors in epithelial ovarian cancer treated with Olaparib - Guo, Xingzi; Tang, Jie; He, Haifeng; Jian, Lian; Qiang, Ouyang; Xie, Yongzhi (Frontiers in Oncology, 2024)
Epithelial ovarian cancer (EOC) remains a leading cause of gynecological cancer deaths.Although Olaparib, a PARP inhibitor, has shown promising results as a maintenance therapy for EOC, the therapeutic response varies among patients. In this retrospective study, we conducted a comprehensive analysis of 133 EOC patients receiving initial Olaparib treatment to investigate the prognostic value of body composition and systemic inflammation variables. Progression-free survival (PFS) was analyzed using the Kaplan-Meier method and Cox proportional hazards regression. Pre-treatment computed tomography images were analyzed to evaluate body composition, including the subcutaneous adipose tissue index (SATI), visceral adipose tissue index (VATI), skeletal muscle area index (SMI), and body mineral density (BMD). Inflammatory markers, such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), serum albumin, and hemoglobin levels, were also measured. The median follow-up years of patients was 16 months (range: 5-49 months). The survival analyses revealed that high SATI, high VATI, high SMI, high BMD, low NLR, and low PLR were associated with a lower risk of disease progression (all p < 0.05). Multivariate analysis identified second or further lines therapy (HR = 2.16; 95% CI = 1.09-4.27, p = 0.027), low VATI (HR = 3.79; 95% CI = 1.48-9.70, p = 0.005), low SMI (HR = 2.52; 95% CI = 1.11-5.72, p = 0.027), low BMD (HR = 2.36; 95% CI = 1.22-4.54, p = 0.010), and high NLR (HR = 0.31; 95% CI = 0.14-0.69, p = 0.004) that were independently associated with poor PFS. The survival analyses for patients with serous adenocarcinoma were comprehensively conducted, revealing that among all clinical parameters, SATI, VATI, SMI, PLR, and NLR exhibited distinct capabilities in distinguishing between two groups. In conclusion, body composition and inflammation variables have the potential to predict the therapeutic response to Olaparib in EOC patients.